North Caucasian Federal District: Conditions and Strategic Reference Points of Development - L. I. Ushvitsky; V. M. Guryanov; N. N. Kunitsyna; S. V. Zenchenko; E. A. Zolotova; V. N. Borozenets (Управленческие науки, 2017)
The authors have carried out the analysis of the North Caucasian Federal District economy in a number of the directions: a general economic situation in the region, investment activity and investment appeal, the diagnostics of the budget stability and budget independence has been performed. They draw the conclusion that the economy of the district has a pronounced non-productive nature, its developed structure and disproportions interfere with forming the stable results and growth of the citizens’ welfare. There are no institutional conditions for the development, a lot of problems with uncoordinated migration flows and logistic disproportions in the region. In order to solve the mentioned problems the concept and the district’s development strategic reference points are offered in the article. One of them is the organization and enhancement of regional clusters. Besides, the forward monotowns dynamics, forming the cross-industry balance, increase in the capacity of the macroregion as a transport (transit) corridor and solving the problems of logistic disproportions through updating and creating the mainstream infrastructure, as well as implementation of a funding mechanism for infrastructure projects are important.